The Use of Nanofluids for Enhancing the Thermal Performance of Stationary Solar Collectors: A Review - Mahmud Jamil, Muhammad; Isa Adamu, Muhammad; Nor Azwadi, Che Sidik; Muhammad Noor Afiq Witri, Muhammad Yazid; R., Mamat; G., Najafi (Elsevier, 2016)
Nanofluid, an advanced type of fluid containing small quantity of nanoparticles (usually less than 100 nm), has been proven to provide more efficient heat transfer compared to conventional fluids. The dispersion of a small amount of solid nanoparticles in conventional fluids such as water or ethylene glycol changes their thermal conductivity remarkably. Recently, nanofluid has been used as a heat transfer fluid to enhance the performance of solar collector devices. This paper reviews recent progress and applications of nanofluids in stationary solar collectors. In addition to reviewing the efficiency of solar collectors which use nanofluids, the paper also discusses the impact of nanofluid usage in solar collector based on economic and environmental viewpoints. Finally, the challenges and future trends related to the application of nanofluids in thermal solar collector is discussed.